Antibacterial Activity of Polyoxometalates Against Moraxella catarrhalis - Gumerova, Nadiia I.; Al-Sayed, Emir; Krivosudský, Lukáš; Čipčić-Paljetak, Hana; Verbanac, Donatella; Rompel, Annette (Frontiers in Chemistry, 2018)
The antibacterial activity of 29 different polyoxometalates (POMs) against Moraxella catarrhalis was investigated by determination of the minimum inhibitory concentration (MIC). The Preyssler type polyoxotungstate (POT) [NaP5W30O110]14‒ demonstrates the highest activity against M. catarrhalis (MIC = 1 µg/ml) among all tested POMs. Moreover, we show that the Dawson type based anions, [P2W18O62]6‒, [(P2O7)Mo18O54]4‒, [As2Mo18O62]6‒, [H3P2W15V3O62]6‒ and [AsW18O60]7‒ are selective on M. catarrhalis (MIC range of 2–8 µg/ml). Among the six tested Keggin type based POTs ([PW12O40]3‒, [H2PCoW11O40]5‒, [H2CoTiW11O40]6‒, [SiW10O36]8‒, [SbW9O33]9‒, [AsW9O33]9‒), only the mono-substituted [H2CoTiW11O40]6‒ showed MIC value comparable to those of the Dawson type group. Polyoxovanadates (POVs) and Anderson type POMs were inactive against M. catarrhalis within the tested concentration range (1‒256 µg/ml). Four Dawson type POMs [P2W18O62]6‒, [(P2O7)Mo18O54]4‒, [As2Mo18O62]6‒, [H3P2W15V3O62]6‒ and the Preyssler POT [NaP5W30O110]14‒ showed promising antibacterial activity against M. catarrhalis (MICs < 8 µg/ml) and were therefore tested against three additional bacteria, namely S. aureus, E. faecalis and E. coli. The most potent antibacterial agent was [NaP5W30O110]14‒, exhibiting the lowest MIC values of 16 µg/ml against S. aureus and 8 µg/ml against E. faecalis. The three most active compounds ([NaP5W30O110]14‒, [P2W18O62]6‒ and [H3P2W15V3O62]6‒) show bacteriostatic effects in killing kinetics study against M. catarrhalis. We demonstrate, that POM activity is mainly depending on composition, shape and size, but in the case of medium-size POTs (charge is more than –12 and number of addenda atoms is not being higher than 22) its activity correlates with the total net charge.